2005
DOI: 10.1007/s11103-004-7204-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel glucosyltransferase involved in steroid saponin biosynthesis in Solanum aculeatissimum

Abstract: Steroidal saponins are widely distributed in many plant species. Their diverse structures have resulted in a wide range of applications, including drug and medicine production. It has been suggested that the nature of the non-saccharide and oligosaccharide portions of the saponin molecule both contribute to the properties of individual saponins. Despite numerous studies on the occurrence, chemical structure, and varying pharmaceutical activities of steroidal saponins, their biosynthesis pathway is poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 42 publications
0
35
1
2
Order By: Relevance
“…Wide ranges of steroidal saponins are synthesized in this genus. It was reported that SaGT4A glucosylate steroidal saponins as well as steroidal alkaloids in Solanum aculeatissimum (Kohara et al 2005) while StSGT a glycosyltransferase from Solanum tuberosum share 75% sequence homology with SaGT4A only glycosylate steroidal alkaloids (Moehs et al 1997). It was reported that fructose was added to furostan saponins at the position of C6-OH of 26-O-β-d-glucopyranosyl by β-fructosidase enzyme of a microbial strain of Arthrobacter nitroguajacolicus.…”
Section: Later Step Modification Enzymes (P450 and Ugt)mentioning
confidence: 99%
“…Wide ranges of steroidal saponins are synthesized in this genus. It was reported that SaGT4A glucosylate steroidal saponins as well as steroidal alkaloids in Solanum aculeatissimum (Kohara et al 2005) while StSGT a glycosyltransferase from Solanum tuberosum share 75% sequence homology with SaGT4A only glycosylate steroidal alkaloids (Moehs et al 1997). It was reported that fructose was added to furostan saponins at the position of C6-OH of 26-O-β-d-glucopyranosyl by β-fructosidase enzyme of a microbial strain of Arthrobacter nitroguajacolicus.…”
Section: Later Step Modification Enzymes (P450 and Ugt)mentioning
confidence: 99%
“…We used the nucleic acid sequence of the GT reported to glycosylate SAs in potato (St-SGT1; McCue et al, 2005) and identified three similar GTs from tomato (GAME1 to 3). In a phylogenetic analysis based on the publicly available full-length GT amino acid sequences (see Supplemental Figure 1 and Supplemental Data Set 1 online), these three tomato proteins formed a separate clade with GTs from potato (St-SGT1-3) that use SAs and two Solanum aculeatissimum proteins (Sa-GT4A and Sa-GT4R) shown to use both SAs and steroidal saponins as sugar acceptors (Moehs et al, 1997;Kohara et al, 2005;McCue et al, 2005McCue et al, , 2006McCue et al, , 2007. In this clade, the three GAME proteins each clustered most closely with one of the potato SGT proteins.…”
Section: Game1 Is Part Of a Clade Of Sa And Steroidal Saponin Gtsmentioning
confidence: 99%
“…Phylogenetic analysis indicated that Sg-1 a and Sg-1 b are classified in a phylogenetic group known as cluster IIIa represented by flavonoid 7-O-glycosyltransferases (Noguchi et al, 2008) (Figure 5C). More importantly, this cluster was found to include a subcluster composed of various triterpene/ phytosterol-related glycosyltransferases from Fabaceae and Solanaceae (e.g., M. truncatula UGT73K1 and UGT73F3; soybean SGT2/UGT73P2 for saponin; tomato [Solanum lycopersicum] GAME1 [UGT73L5], GAME2 [UGT73L4], and GAME3 [UGT73L6]; potato [Solanum tuberosum] SGT1, SGT2, and SGT3; and Solanum aculeatissimum GT4A for steroidal saponin) (Moehs et al, 1997;Achnine et al, 2005;Kohara et al, 2005;McCue et al, 2005McCue et al, , 2006McCue et al, , 2007Naoumkina et al, 2010;Shibuya et al, 2010;Itkin et al, 2011). Sg-1 a (UGT73F4) and Sg-1 b (UGT73F2) genes apparently show structural similarity to M. truncatula saponin glucosyltransferase UGT73F3 (Naoumkina et al, 2010).…”
Section: Phylogenetics Of Sg-1 Proteinsmentioning
confidence: 99%